2019
DOI: 10.1002/anie.201911637
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metastable Pentavalent Plutonium Solid Phase on the Pathway from Aqueous Plutonium(VI) to PuO2 Nanoparticles

Abstract: Here we provide evidence that the formation of PuO 2 nanoparticles from oxidized Pu VI under alkaline conditions proceeds through the formation of an intermediate Pu V solid phase,s imilar to NH 4 PuO 2 CO 3 ,w hich is stable over ap eriod of several months.F or the first time,s tate-of-the-art experiments at Pu M 4 and at L 3 absorption edges combined with theoretical calculations unambiguously allowt od etermine the oxidation state and the local structure of this intermediate phase.Supportinginformation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 34 publications
(41 reference statements)
8
58
0
Order By: Relevance
“…The effects of the initial chemical conditions, polymerisation of the initial Th IV precipitates and the stability of the NPs overt ime can be addressedw ith this methodology.T he latter is of particular interest because ThO 2 NPs, in contrast to NPs of other actinided ioxides synthesised by the same chemistry route, show an increase in size and crystallinity over time (ageing effect) depending on the conditions. Our findings on ThO 2 ,i nc omparison with recentr esults on CeO 2 [65] and PuO 2 [15,16] NPs synthesised under similarc onditions, show differences in systems that are often indicated as very similar. The fact that thorium haso nly one oxidation state, unlike cerium andp lutonium, prevents the accommodation of chargei mbalancew ith oxidation or reduction at selected sites.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The effects of the initial chemical conditions, polymerisation of the initial Th IV precipitates and the stability of the NPs overt ime can be addressedw ith this methodology.T he latter is of particular interest because ThO 2 NPs, in contrast to NPs of other actinided ioxides synthesised by the same chemistry route, show an increase in size and crystallinity over time (ageing effect) depending on the conditions. Our findings on ThO 2 ,i nc omparison with recentr esults on CeO 2 [65] and PuO 2 [15,16] NPs synthesised under similarc onditions, show differences in systems that are often indicated as very similar. The fact that thorium haso nly one oxidation state, unlike cerium andp lutonium, prevents the accommodation of chargei mbalancew ith oxidation or reduction at selected sites.…”
Section: Resultssupporting
confidence: 86%
“…One of the most investigated topics of radiochemistry at the nanoscale is the formationo ft etravalent actinideo xide NPs in aqueous solution. [7][8][9][12][13][14][15][16][17] Tracking their aggregation mechanism under different chemical conditions, identifying the presence of multiple oxidation states and characterising their surfaces are real challenges. Even what is considered the simplest system,T hO 2 ,f or which only the tetravalent oxidation state is stable, is hotly debated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments showed that HERFD measurements at the An M 4 edge, characterized by the An 3d-5f electronic transitions, are very powerful for oxidation state identification. 39,41 Fig . 3 (left) shows the Pu M 4 edge measurements on six PuO 2 NPs samples compared to both the spectrum of a PuO 2 reference and to the results of calculations based on Anderson impurity model (AIM).…”
Section: Resultsmentioning
confidence: 99%
“…The spectral broadening can be further reduced by using an x-ray emission spectrometer for recording the fluorescence lines instead of a conventional solid state detector. To date, this approach has been applied in the field of catalysis 14 , Li-S batteries 15 , and actinides chemistry 16,17 .…”
Section: Introductionmentioning
confidence: 99%